ANALISIS KETIDAKSANTUNAN BAHASA DAN PELANGGARAN MAKSIM DALAM KASUS VIRAL LPDP DI MEDIA SOSIAL - Melati, Arum; Valentina, Feby; Syafira Siregar , Nabila; Erdiyanti , Revalina; Rahimah, Siti (STKIP Subang, 2026)
This study examines language impoliteness and violations of politeness maxims in netizen comments on a viral LPDP case on social media. The problem addressed is the increasing use of impolite language in public digital discussions. The objective of this research is to identify the forms of language impoliteness, types of maxim violations, and how netizens express criticism, satire, and insults. This study employs a descriptive qualitative method with a pragmatic approach. Data were collected through observation and documentation of TikTok comments related to the case, then analyzed using Leech’s Politeness Principle and Grice’s Cooperative Principle. The findings reveal that impoliteness commonly appears in the form of satire, mockery, accusations, and degrading expressions. The most frequently violated maxims are the approbation maxim and tact maxim. These results indicate that netizens tend to deliver criticism in a direct and emotional manner without considering politeness norms, causing public discussions to shift from substantive issues to personal attacks. Therefore, awareness of polite language use is necessary to maintain constructive communication in digital spaces